Ecosystem Changes in the Structure of Socio-Economic Relations - V. A. Chernov (Мир новой экономики, 2022)
The methodological base of the research includes the theoretical foundations of cluster structure, structural integration of ecosystems, the network method of their coordination, platform interaction, global reporting initiative (GRI), international and domestic regulations in the field of sustainable development, scientific publications of Russian and foreign authors. The article proposes clarifications of individual formulations in the definition of ecosystems and conducts their classification: bionomic, industrial ecosystem, business ecosystem, business, innovative ecosystem. The evolution of the definition of “ecosystem” is investigated, in which its qualitatively new stage in the global concept of sustainable development is revealed. The formulation of the ecosystem of sustainable development as the intellectual coordination core of the innovation ecosystem is derived. The concepts of capital components of the new economic formation of “accessism” are introduced. The risks and threats of economic, legal, and state security in the formation of the access economy are investigated. A model of integration of components has been developed: economic, social, environmental, infrastructural elements and directions. The directions of creating new organizational forms of interaction in the ecosystem with the participation of state technology (Gostech) are proposed. Recommendations are given to counter threats and risks caused by ecosystem changes in the structure of socio-economic relations that have historical significance.